Insights into G-Quadruplex-Hemin Dynamics Using Atomistic Simulations: Implications for Reactivity and Folding - Stadlbauer, Petr; Islam, Barira; Otyepka, Michal; Chen, Jielin; Monchaud, David; Zhou, Jun; Mergny, Jean-Louis; Šponer, Jiří (Journal of chemical theory and computation, 2021)
Guanine quadruplex nucleic acids (G4s) are involved in key biological processes such as replication or transcription. Beyond their biological relevance, G4s find applications as biotechnological tools since they readily bind hemin and enhance its peroxidase activity, creating a G4-DNAzyme. The biocatalytic properties of G4-DNAzymes have been thoroughly studied and used for biosensing purposes. Despite hundreds of applications and massive experimental efforts, the atomistic details of the reaction mechanism remain unclear. To help select between the different hypotheses currently under investigation, we use extended explicit-solvent molecular dynamics (MD) simulations to scrutinize the G4/hemin interaction. We find that besides the dominant conformation in which hemin is stacked atop the external G-quartets, hemin can also transiently bind to the loops and be brought to the external G-quartets through diverse delivery mechanisms. The simulations do not support the catalytic mechanism relying on a wobbling guanine. Similarly, the catalytic role of the iron-bound water molecule is not in line with our results; however, given the simulation limitations, this observation should be considered with some caution. The simulations rather suggest tentative mechanisms in which the external G-quartet itself could be responsible for the unique H2O2-promoted biocatalytic properties of the G4/hemin complexes. Once stacked atop a terminal G-quartet, hemin rotates about its vertical axis while readily sampling shifted geometries where the iron transiently contacts oxygen atoms of the adjacent G-quartet. This dynamics is not apparent from the ensemble-averaged structure. We also visualize transient interactions between the stacked hemin and the G4 loops. Finally, we investigated interactions between hemin and on-pathway folding intermediates of the parallel-stranded G4 fold. The simulations suggest that hemin drives the folding of parallel-stranded G4s from slip-stranded intermediates, acting as a G4 chaperone. Limitations of the MD technique are briefly discussed.
Keywords: G-kvadruplexy; Hemin; G-Quadruplexes; Molecular Dynamics Simulation; simulace molekulární dynamiky; hemin; DNA, Catalytic; biokatalýza; DNA katalytická; Biocatalysis